The Synergistic Effects of Solutions Journalism and Corporate Social Responsibility Advertising. Issue 3 (16th March 2021) - Li, Minjie
Abstract: This study explores the synergistic effects of solutions journalism and corporate social responsibility (CSR) advertising. More specifically, it experimentally investigates how news story orientation (i.e., Problem-Oriented, Solution-Oriented) interacts with the relevance of the advertisement (i.e., Irrelevant Non-CSR, Low-Relevance CSR, High-Relevance CSR) displayed alongside the news story to direct people's affective and cognitive responses to the news story and advertisement in the digital sphere. The findings demonstrated that the solution-oriented story elicited more positive affect, issue interest, self-efficacy, intentions of sharing the story on social media or researching the issue, favourable attitudes towards the advertisement and the brand, purchase intention, and recommendation intention. Irrelevant advertising elicited significantly less favourable attitudes towards the advertisement and the brand, purchase intention, and recommendation intention. However, pairing the solution-oriented story with the irrelevant advertisement elicited significantly more brand recall. Theoretical and practical implications for journalism and advertising are discussed.